Characteristics of PM2.5 and secondary inorganic pollution formation during the heating season of 2021 in Beijing - Wang, Jialing; Wu, Lingyan; Sun, Junying; Zhang, Sinan; Zhong, Junting (Frontiers in Environmental Science, 2023)
Water-soluble inorganic ions (WSIIs) were online measured in Beijing during the heating season of 2021, during which Beijing 2022 Olympic and Paralympic Winter Games were hosted. The characteristics of PM2.5 and water-soluble inorganic ions were investigated in general, as well as in clean period, polluted period and Olympic and Paralympic Winter Games. It was found that most of the polluted episodes occurred under conditions of low wind speed, temperature inversion and high relative humidity. The total mass concentration of water-soluble inorganic ions during the polluted period and the clean period accounted for 38.2% and 61.4% of the PM2.5 mass concentration, respectively. Both sulfur oxidation ratio (SOR) and nitrogen oxidation ratio (NOR) showed strong relationship with relative humidity. During the polluted period, the concentrations of secondary aerosols such as sulfate, nitrate and ammonium (SNA) increased significantly. Secondary transformation was enhanced compared with that in the clean period. A polluted process after a snowfall event was selected to explore the mechanism of sulfate and nitrate formation under high relative humidity. The results would be beneficial to understand the causes of pollution and help the government to formulate effective measures to control air pollution in winter.